PENGARUH FORMULASI KARAGENAN DAN PATI SAGU TERHADAP SIFAT FISIK, KIMIA, DAN ORGANOLEPTIK ES KRIM UBI JALAR UNGU - Asrul Karami; Tri Rahayuni; Suko Priyono (Universitas Tanjungpura, 2018)
Purple sweet potato ice cream is an ice cream made from purple sweet potato paste as main ingredient. In general, ice cream production use of stabilizer for effecting the characteristic. One of the ingredients as the stabilizers are carrageenan and sago starch. This research aimed to find out the effect of carrageenan and sago starch formulation on physical, chemical and sensory properties of purple sweet potato ice cream. The research design was using a randomized block design of 1 factor which is comparison different ratios of carrageenan and sago starch that consist of 6 level of treatment (0.5%:0.0% , 0.4%:0.1% , 0.3%:0.2%, 0.2%:0.3%, 0.1%:0.4 and 0.0%:0.5%) with 4 replication. The research showed that the most preferred of ice cream at carrageenan 0% and sago starch 0.5% formulation with the physical (melting time is 2.01 minute/g, the viscosity is 4.25 d.PaS and overrun 38.79%), the chemical (11.11% of fat and 34.60°Brix of TDS), and sensory such as aroma 3.77(like), taste 4.03 (like), and texture 3.80 (like)